Egypt’s Quest for Hydro Hegemony and the Changing Power Relation in the Eastern Nile Basin - Endaylalu, Gashaw Ayferam (Ethiopian Journal of Social Sciences, 2019)
This paper examines incessant hydro hegemonic power configuration and the changing power relation in the Eastern Nile basin. The hydro politics of Nile has been at the centre of academic debates for long and several scholars, in this regard, have studied the multifarious aspects of the hydro-politics of Nile River with different opportune contentious issues. However, little attention has been given to the study of hydro hegemony and counter hydro hegemony in the aforesaid river basin. The overall objective of this paper is, therefore, to examine the hydro hegemonic strategies and tactics used by Egypt in its long journey of establishing, maintaining and consolidating the current hydro political status quo. Methodologically, the study employed qualitative research method. In view of that, the study used both primary and secondary sources of data. The primary data was collected through key informant interviews while the secondary data was collected from books, archival sources. Given the data gathered are qualitative; the study employed the qualitative data analysis techniques of historical narrative, and document and critical discourse analysis. The paper argues that Egypt has used a smart power, a combination of hard and soft power, in establishing, maintaining and consolidating its most preferable state of affairs, and in the meantime there is no pragmatic change but only sign of changes foreshadowing a new order which can be explained by the post 1990s changing domestic, regional and international environment. This anticipated new order, however, is now infested with the hegemonic power using hegemonic compliance producing mechanism and thus it is in between life and death. Thus, there is a need on the part of non-hegemonic riparians to use smart power, a combination of hard and soft power, so as to successfully transform the established order. First, there is a need for ‘decolonizing the hegemonic mentality’ to affirm that ‘Egypt is not the sacred husband of Nile rather Nile has made a geographical and legal marriage with 11 countries’. Second, there is a need for the establishment of a ‘historic non-hegemonic block’ in order to bring consistent unified upstream position which will push for a paradigmatic change. Failing to do so would mean endorsing the current hegemonic status quo and calling for the extinction of the commonly shared resource_ the Nile waters.